Physicochemical and Sensory Characterization of Instant Porridge Based on Sago, Pumpkin, and Soybean Flour at Various Drying Temperatures - Slamet, Agus; Purwaningsih, Heni (Journal of Food and Agricultural Product, 2025)
This study aims to determine the effect of variations in the ratio of ingredients and drying temperature on the quality of instant porridge based on sago, pumpkin, and soy flour. The ratio of raw materials used: 1:1:1, 1:2:1, and 1:3:1. The drying temperature ratios used were 130, 140, and 150°C. Physical properties of instant porridge were tested: yield, slurry density, rehydration power, oil absorption capacity, and color. Chemical analysis included: moisture content, ash, protein, fat, carbohydrate, beta-carotene, total phenol, and antioxidant activity. Organoleptic testing of color, aroma, taste, viscosity, and overall acceptance. The results showed that instant porridge with a ratio of 1:2:1 and a drying temperature of 130°C was most favored by panelists. The physical properties of the instant porridge, consisting of slurry density, rehydration, oil absorption capacity, and color, met the requirements. The instant porridge had the following chemical composition: moisture content 6.31%, protein 24.67%, fat 2.16%, ash 4.89%, and carbohydrate 61.97%. The beta-carotene content, total phenolics, and antioxidant activity were 43.25 µg/g, 14.64 mg EAG/g, and 33.09% RSA, respectively. The instant porridge produced has potential as a healthy functional food. Keywords: instant porridge, sago, pumpkin, soy flour, functional food